Estimation Of The Carbon Potential In The Above Ground At The Stand Level Poles And Trees In Sentajo Protected Forest - Pebriandi '; Evi Sribudiani; Mukhamadun ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Natural forest has many ecological functions which plays a vital role in preserving the ecosystem balance. One of them is to stabilize the climatic condition. This is linked with the forest capability to absorb carbondioxide in the photosynthesis process. The more carbondioxide absorbed and stored in the form of biomass carbon, the more it reduces greenhouse gas effect in the atmosphere. This research aimed to obtain information about the value of biomass and carbon content in the Sentajo Protected Forest. Above ground biomass estimation was done by establishing nine plots with the size 20 m x 20 m. Trees with dbh ≥ 10 cm were recorded in terms of diameter and identification species. Tree biomass was estimated by employing Ketterings et al, (2001). Sentajo Protected Forest region has great potential in storing carbon stocks. The study results showed that carbon contain in Sentajo Protected Forest is 223,177 ton/ha. Keywords : forest, carbon, biomass.